Le retour de Karl Friedrich Schinkel à Berlin : la reconstruction de la Bauakademie - Isabelle Weis (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The aim of this article is to contribute to the thought about this project of rebuilding Schinkel’s Bauakademie in Berlin in the nineteen century. At the end of 2017, architects had to show their ideas in a context with the motto: “Schinkel as much as possible” in order to create at first spaces, for which they have defined the programs. Such a rebuilding project has brought a matter up for discussion about the conception of architecture between historical break and continuity. This text tries to set out the capacity and difficulties of conceiving the intern and extern structure of an institution which has to rank as one of the international leaders in the art and in the art of architecture without erasing Berlin’s architecture history.